The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mnfr.201800219
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Dysregulates Hypothalamic‐Pituitary Axis Gene Expression Levels which are Differentially Rescued by EPA and DHA Ethyl Esters

Abstract: A HF diet can affect H-P axis transcription, which can be mitigated in some genes by EPA and DHA, but not fish oil in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…To lead this process, known also as oogenesis, the female gonads enroll cells surrounding the oocyte, which constitute the somatic compartment of the ovarian follicle unit. Specifically, a finely regulated release of endocrine and paracrine factors, acting on and released from the theca and granulosa cell layers of the follicle, are required for the completion of a synchronous follicle–oocyte development during the estrous or menstrual cycle in mammals [ 14 , 15 , 16 ].…”
Section: High-fat Diet Influence On Female Reproductive Endocrine Con...mentioning
confidence: 99%
“…To lead this process, known also as oogenesis, the female gonads enroll cells surrounding the oocyte, which constitute the somatic compartment of the ovarian follicle unit. Specifically, a finely regulated release of endocrine and paracrine factors, acting on and released from the theca and granulosa cell layers of the follicle, are required for the completion of a synchronous follicle–oocyte development during the estrous or menstrual cycle in mammals [ 14 , 15 , 16 ].…”
Section: High-fat Diet Influence On Female Reproductive Endocrine Con...mentioning
confidence: 99%
“…(23) In addition, a genetic study suggested that a high-fat diet not only affect the HPA axis but also alters all hormonal axis regulated by the pituitary gland which causes the augmentation of corticosterone production as a result of POMC gene transcription multiplication. (24) Our results indicate that a high-protein diet has the benefit of keeping the blood corticosterone level low. Indeed, young males who undergo strenuous training reportedly achieved low blood cortisol levels after consuming whey protein for six weeks.…”
Section: Discussionmentioning
confidence: 60%
“…DHA, which induces apoptosis by significantly increasing the ratio of cyclic (c)AMP/cGMP levels and promoting the expression of TLR-4 and PPAR-α in breast cancer, 52 also influences the expression of multiple HPA genes that are susceptible to the effects of high fat diet. 53 Metabolite kynurinine was dysregulated in NFPA samples and promoted brain tumor progression through local AhR activation. 54 These altered pathways and metabolites cause dysregulation of various important processes like angiogenesis, proliferation, cell cycle regulation, and apoptosis to promote progression of NFPA.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Metabolite docosahexaenoic acid (DHA), an omega 3 fatty acid, was mapped to a metabolic and signal transduction pathway, which is the product of alpha-linolenic acid. DHA, which induces apoptosis by significantly increasing the ratio of cyclic (c)­AMP/cGMP levels and promoting the expression of TLR-4 and PPAR-α in breast cancer, also influences the expression of multiple HPA genes that are susceptible to the effects of high fat diet . Metabolite kynurinine was dysregulated in NFPA samples and promoted brain tumor progression through local AhR activation .…”
Section: Discussionmentioning
confidence: 99%